KENABIAN: PRESPEKTIF FILSAFAT ISLAM - Noor, Fauz (Program Studi Hukum Tata Negara, 2024)
In the doctrine of faith in Islam, faith in the Holy Scriptures and faith in the Prophets are known. The philosophical value of these two doctrines, because humans after